1990
DOI: 10.1002/ajpa.1330820108
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the Jirels: Patterns of mate choice

Abstract: The influence of mating practices on genetic structure has been an area of great interest for anthropologists. In this paper, the techniques of potential mates analysis are employed to explore the mating patterns observed among the Jirels, a tribal population of eastern Nepal. Genealogical, anthropometric, dermatoglyphic, and demographic data for members of seven Jirel villages are used. Potential mate pools for a sample of 268 females are enumerated by village. Age structure and the Jirel restriction against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The population has been the subject of detailed genetic study since 1985 (23,24), which has resulted in a wealth of pedigree information. These extensive genealogical records allowed assignment of all 444 individuals to a single pedigree that was very powerful for genetic analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population has been the subject of detailed genetic study since 1985 (23,24), which has resulted in a wealth of pedigree information. These extensive genealogical records allowed assignment of all 444 individuals to a single pedigree that was very powerful for genetic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The focal population for these studies was the Jirel population of eastern Nepal, a Tibeto-Burman language speaking hybrid group derived from Sherpas and Sunwars approximately 10-11 generations ago (23,24). We used data on Ascaris egg counts in a single large pedigree comprising 1,261 members of the Jirel population to determine that genetic factors accounted for approximately 30% (h 2 ϭ 0.291, P Ͻ 0.0001) of the variation in eggs per gram of feces (EPG) as assessed by the Kato-Katz thick smear method (22).…”
mentioning
confidence: 99%
“…The population has been the subject of extensive population genetic and genetic epidemiologic study for the last 14 years and has this has resulted in detailed knowledge of the pedigree structure of the group. [34][35][36][37][38][39][40][41][42][43][44][45] Family information. Household surveys were performed to obtain demographic, pedigree, and socioeconomic data from each household.…”
Section: Population Materials and Methodsmentioning
confidence: 99%
“…In the Jirels, observed population structure effects are probably owing to the residual effects of differential admixture with relatively closely related ancestral populations including Sherpas and Sunwars. Additionally, the relative endogamy of Jirel villages [11,25] and the non-randomness of clan-structured migration [21] lead to a second type of lesser microdifferentiation generating local between-group genetic differences. We appear to have observed some of this between-group genetic variation as relevant for our helminthic infection-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The study was based in the Jiri region of Dolakha district in the eastern hills of Nepal, and focused on the Jirel ethnic group. Some ethnohistorical accounts and population genetic studies have suggested that this ethnic group is a hybrid population derived from Sunwars and Sherpas [10,11]. Members of the Jirel population were sampled from across seven villages in the Jiri region.…”
Section: Introductionmentioning
confidence: 99%